Green marketing orientation and environmental and social performance of hospitality firms in South Africa - Olawale Fatoki (Foundations of Management, 2019)
The pressure on businesses to engage not only on profitability but also on social and environmental responsibility has increased in recent times. The study empirically tested the relationship between green marketing orientation (GMO) and environmental and social performance in the context of firms in the hospitality industry. Sustainable performance measurement focuses not only on financial but also on social and environmental performance. The study used the quantitative research design, and the cross-sectional survey method was used for data collection from 192 respondents. Descriptive statistics, Pearson correlation, and regression analysis were used for data analysis. Cronbach's alpha was used as a measure of reliability. The results indicated a significant positive relationship between GMO and environmental and social performance of hospitality firms. The findings of the study suggest that GMO is a firm-level strategic resource that can improve the sustainable performance of firms in the hospitality sector. Theoretically, the study linked GMO to environmental and social performance of firms. Empirically, the study adds to the literature on the effect of GMO on sustainable performance. Practically, the study suggested recommendations that can improve the adoption of GMO by firms. These include green design, green positioning, green supply chain, and green strategy.
Keywords: M10; M13; M14; M31; 650; green marketing orientation; environmental; social; performance; hospitality; tourism; South Africa